ANALISIS TOTAL PRODUCTIVE MAINTENANCE DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS DAN SIX BIG LOSSES DI PT X - Wijaya, Chandra; Sukania, I Wayan; Adianto (Universitas Tarumanagara, 2023)
PT. X is a company founded in 2010, this company is engaged in printing and packaging. The maintenance system implemented by PT. X is preventive maintenance. However, the JK-650PC glue machine has a considerable downtime that affects the company's productivity level. Therefore, this study aims to solve these problems by analyzing Total Productive Maintenance (TPM) with the method of Overall Equipment Effectiveness and Six Big Losses on this production machine. The results of the calculation show the average OEE value of PT. X during July 2021 to June 2022 was 60.53% due to a very low average performance efficiency value of 68.648%. And the dominant factor that causes the biggest losses on the JK-650PC machine is reduce speed losses, which is an average of 27.13%. The improvement proposal given based on Total Productive Maintenance (TPM) analysis is autonomous maintenance (standard operational procedure), planned maintenance (daily checklist), and training and education (planning internal training program).